72.9k views
19 votes
The expression 2x^2+5x-12 is equivalent to which of the following?

a
(2x-3)(x+4)

b
(x+3)(2x-4)

c
(2x-3)(2x+2)

d
(2x+3)(x-4)

User Muthukumar
by
5.5k points

2 Answers

6 votes

Answer:

letter D

Explanation:

2

x

2

5

x

12

We can Split the Middle Term of this expression to factorise it.

In this technique, if we have to factorise an expression like

a

x

2

+

b

x

+

c

, we need to think of 2 numbers such that:

N

1

N

2

=

a

c

=

2

12

=

24

and,

N

1

+

N

2

=

b

=

5

After trying out a few numbers we get:

N

1

=

8

and

N

2

=

3

3

(

8

)

=

24

, and

3

+

(

8

)

=

5

2

x

2

5

x

12

=

2

x

2

8

x

+

3

x

12

=

2

x

(

x

4

)

+

3

(

x

4

)

(

x

4

)

is a common factor to each of the terms

=

(

2

x

+

3

)

(

x

4

)

User Ataylor
by
5.2k points
4 votes

Answer:

a see below for explanation

Explanation:

2x^2 + 8x - 3x - 12

2x^2 +5x - 12

User Gabriel Southern
by
6.0k points